Microscopical studies of necrotising scleritis. I. Cellular aspects. Issue 11 (November 1984) - Young, R. D.; Watson, P. G.
Abstract : Light and electron microscopy were used to examine tissue excised during surgery from eight patients with advanced destructive scleral disease. These comprised two cases of scleromalacia perforans, three cases of anterior necrotising scleritis alone or in conjunction with other systemic diseases, and three cases in which scleritis developed following ocular surgery. It was not possible to distinguish between these three categories by histological or cytopathological criteria. All showed extensive granulomatous infiltration of the conjunctiva, episclera, and sclera by plasma cells and lymphocytes. Mast cells were abundant throughout these inflamed tissues. Examination of scleral stroma from sites in advance of the granuloma revealed active fibroblastic cells in the absence of other inflammatory cells. Fibroblastic transformation of scleral cells may be one of the earliest events in scleral degradation during necrotising disease.